A low noise low offset CMOS signal conditioning circuit and a real-time interface algorithm for infrared sensor system - Juanda. (2010)
The final year project pertains to the design of a low-noise low-offset signal conditioning amplifier and a development of algorithms for imaging processing and displaying. This project is part of an on-going collaborative research project between Massachusetts Institute of Technology and Nanyang Technological University on the development of a Multispectral Infrared Detector Arrays on Read-Out Integrated Circuit (MIDAS-on-ROIC) The signal conditioning amplifier is one of the most critical block to interface the infrared sensor. On the basis of a chopper stabilization technique, the proposed design features the low noise of 13 nV/√Hz @1Hz, the low offset of 50nV, and low power of 264μW. To achieve the low noise attribute at the optimized cost and power dissipation, several novel techniques and topologies are proposed including the novel chopper demodulator, the novel amplifier topology, and the novel technique to optimize the area and the power dissipations. Further, the flicker and thermal noise expressions for the designed amplifier are also derived and pertinent parameters are delineated. The designed signal conditioning amplifier is verified by means of computer simulations. The algorithms to construct and display real-time images are also realized. Further, a user-friendly Graphical User Interface is realized in MATLAB code. The interface between the DSP board and the computer is also realized for data synchronization by using a VHDL code. In summary, the hardware design and software programming embodied in this projectare not only a comprehensive training exercise, but also are the real post-graduate research experience. The outcomes of this project are very important and significant to the on-going project of MIDAS-on-ROIC.